Нужно решить: 5.6-3(2-0.4х)=0.4(4х+1)

eduardpiterskiy eduardpiterskiy    3   28.06.2019 05:00    0

Ответы
serzh1425 serzh1425  02.10.2020 13:35
5.6-3(2-0.4х)=0.4(4х+1) ;
5.6 -6 +1.2x =1.6x + 0.4 ;
5.6 -6 -0.4 =1.6x  - 1.2x  ;
- 0.8 =0.4x
x = (-0.8)/0,4;
x= - 2.    

5,6-3(2-0,4х)=0,4(4х+1) ;
5,6 -6 +1,2x =1,6x + 0.4 ;
5,6 -6 -0,4 =1,6x  - 1,2x  ;
- 0,8 =0,4x
x = (-0,8)/0,4;
x= - 2. 
ПОКАЗАТЬ ОТВЕТЫ
Диана149018 Диана149018  02.10.2020 13:35
5.6-6+1.2х=1.6х+0.4 и 1.2 х-1.6х=0.4+0.4 и -0.4х=0.8 и х=-2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика